2008
DOI: 10.1523/jneurosci.3024-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response in the Hippocampus of PS1M146L/APP751SLMouse Model of Alzheimer's Disease: Age-Dependent Switch in the Microglial Phenotype from Alternative to Classic

Abstract: Although the microglial activation is concomitant to the Alzheimer's disease, its precise role (neuroprotection vs neurodegeneration)has not yet been resolved. Here, we show the existence of an age-dependent phenotypic change of microglial activation in the hippocampus of PS1xAPP model, from an alternative activation state with A␤ phagocytic capabilities (at 6 months) to a classic cytotoxic phenotype (expressing TNF-␣ and related factors) at 18 months of age. This switch was coincident with high levels of solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
347
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(380 citation statements)
references
References 69 publications
28
347
2
3
Order By: Relevance
“…As expected (Jimenez et al, 2008; Serrano‐Pozo, Muzikansky, et al, 2013; Serrano‐Pozo, Betensky, Frosch, & Hyman, 2016; Trujillo‐Estrada et al, 2013), the hippocampus of both the transgenic APP/PS1 model and Alzheimer's patients (Braak V–VI) displays significant astrogliosis (measured by GFAP expression and by the area covered by the reactive astrocytes; see also Jimenez et al, 2008), which progresses in parallel to the extracellular amyloid pathology. The increase in astrocytic reactivity involves both morphological (enlarged cell body and processes) and molecular changes (Osborn et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As expected (Jimenez et al, 2008; Serrano‐Pozo, Muzikansky, et al, 2013; Serrano‐Pozo, Betensky, Frosch, & Hyman, 2016; Trujillo‐Estrada et al, 2013), the hippocampus of both the transgenic APP/PS1 model and Alzheimer's patients (Braak V–VI) displays significant astrogliosis (measured by GFAP expression and by the area covered by the reactive astrocytes; see also Jimenez et al, 2008), which progresses in parallel to the extracellular amyloid pathology. The increase in astrocytic reactivity involves both morphological (enlarged cell body and processes) and molecular changes (Osborn et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…These bigenic mice were obtained (see Blanchard et al, 2003) by crossing homozygous PS1 mice (expressing human mutant PS1[M146L] under HMGCoA reductase promoter) to hemizygous APP751SL mice (expressing human mutant APP751 carrying the Swedish [KM670/671NL] and London [V717I] mutations under the control of the Thy1 promoter). We have previously characterized this APP/PS1 transgenic model (Baglietto‐Vargas et al, 2010; Jimenez et al, 2008; Ramos et al, 2006; Sanchez‐Varo et al, 2012; Torres et al, 2012; Trujillo‐Estrada et al, 2014). Age‐matched non‐transgenic mice (WT) of the same genetic background (C57BL:6) were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…A␤ oligomers have been demonstrated to cause these pathological changes in vitro when applied exogenously to cultured cells and brain slices (Hu et al, 1998;Lambert et al, 1998;Kayed et al, 2003;De Felice et al, 2008;Jimenez et al, 2008). However, it is still unclear whether A␤ oligomers have similar pathological effects in vivo.…”
Section: Abnormal Tau Phosphorylation In App E693⌬ -Tg Micementioning
confidence: 99%
“…Several studies have demonstrated that exogenously applied A␤ oligomers induce tau hyperphosphorylation (De Felice et al, 2008), activate astrocytes (Hu et al, 1998) and microglia (Jimenez et al, 2008), and cause neuronal death (Lambert et al, 1998; in vitro. However, in animal models, these findings have never been observed before amyloid plaque deposition (for review, see Duyckaerts et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…M1 microglia are considered to be pro-inflammatory (releasing IL-1β, TNFα) and result in deleterious neuroinflammation while M2 (releasing IL-10, neurotrophins) are believed to promote neuroprotection and regeneration after injury (Olah et al, 2011, David and Kroner, 2011, Jimenez et al, 2008. Although minocycline is well-regarded as an inhibitor of microglial activation, recent evidence indicates that minocycline selectively inhibits microglial M1, but not M2, polarisation both in vitro and in an animal model of amyotrophic lateral sclerosis (Kobayashi et al, 2013).…”
Section: Chronic Minocycline Differentially Alters Microglial Phenotymentioning
confidence: 99%